Dampak Tata Kelola Perusahaan Terhadap Kebijakan Pembayaran Dividen Pada Perusahaan Manufaktur - Veren Velicia Natalie; Yunita Kusumaningrum; Henny Setyo Lestari (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This research paper scrutinizes the influence of corporate governance which was one of the determinants of dividend payments policy. A total of 195 manufacturing companies listed on the Indonesia Stock Exchange were used for the sample of this research and used 5 years period starting from 2016 to 2020. The data used in this paper is secondary data and the sampling method is using the purposive sampling method. The panel data regression method is used for this research to test the influence of independent variables on the dependent variables. The outcome of this study reveals that board gender diversity and return on asset ratio (ROA) have a negative effect on the dividend payout ratio (DPR). However, board size and leverage have no effect on the dividend payout ratio (DPR). This research expected to provide information and overview to investors in making an investment decision to pay attention to corporate governance because it's has an impact on the firm's dividend payout policy.